2023
DOI: 10.3390/electronics12071567
|View full text |Cite
|
Sign up to set email alerts
|

Compact-Transmission-Line Decoupling and Matching Network of Three-Element Array for Wireless Applications

Abstract: In this paper, a compact-transmission-line (TL) decoupling and matching network (DMN) for three-element circular arrays is presented. As a result of the miniaturization of wireless terminals, the antenna spacing is too close, leading to large couplings and deteriorating system performance. The DMN consists of an impedance transformation section and a star-shaped neutralization section which eliminates couplings between antennas while occupying a smaller area. The impedance transformation section converts the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The mutual coupling could also be reduced by directly orthogonal arrangement of antenna elements in [14,15]. The decoupling network was reported in [16,17]. In addition, several studies on metasurfaces have been reported in [18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…The mutual coupling could also be reduced by directly orthogonal arrangement of antenna elements in [14,15]. The decoupling network was reported in [16,17]. In addition, several studies on metasurfaces have been reported in [18][19][20].…”
Section: Introductionmentioning
confidence: 96%